Strategi Public Relation PT Sari Melati Kencana Dalam Mengukuhkan Brand Image Pada Pizza Hut Bengkulu - Delvi Iranda; Sapta Sari; Anis Endang SM (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to determine the Public Relations Strategy of PT Sari Melati Kencana in strengthening the Brand Image of Pizza Hut Bengkulu. This research uses PR Strategy theory which includes operational strategy, educational persuasive approach, social responsibility approach to public relations and PR, cooperative approach, and coordinative or integrative approach. And the type of research used is qualitative research. The results of this research show that PT Sari Melati Kencana's public relations in strengthening the brand image of Pizza Hut Bengkulu depicts a holistic and integrated effort. An operational strategy that prioritizes a social approach, a persuasive and educational approach that creates educational and persuasive communication, a public relations social responsibility approach that responds quickly to complaints and maintains product quality, a cooperative approach that fosters internal and external harmonious relationships, and a coordinative or integrative approach which makes a positive contribution to increasing community support, customer loyalty and strengthening a positive image. Overall, a PR strategy that includes these aspects has succeeded in having a positive impact on the image and popularity of Pizza Hut Bengkulu, creating positive relationships with customers and strengthening their position in the culinary industry.